How Does AI Influence Financial Risk Management and Investment Decisions? - Kazem, Sumaya Ali (Technium Social Sciences Journal, 2025)
The study aims to study the effectiveness of using artificial intelligence in multi-management and its impact on investment accuracy. A questionnaire was designed as a study tool, divided into three principal axes and hypotheses related to the effectiveness of artificial intelligence and its multifaceted financial impact, as well as its effect on investment accuracy. The reliability and validity of the questionnaire were evaluated using Van Cronbach's alpha (Cronbach's alpha). The results concluded that there is a significant relationship between artificial intelligence and multi-management and investment decisions (R = 0.937), as well as a powerful relationship between the specific trade-off value (R Square), which explains 87.8% of the variance in primary investment accuracy. It was concluded from the differences in primary intelligence accuracy that the two independent variables (dependent artificial intelligence) have a definite and direct impact on the variable (investment decisions). The results confirm that the use of artificial intelligence techniques contributes effectively to multi-management, leading to more successful investments.